1997
DOI: 10.1080/15216549700203841
|View full text |Cite
|
Sign up to set email alerts
|

Activation of macrophages by lactoferrin: secretion of TNF‐α, IL‐8 and NO

Abstract: When macrophages were cultured with lactoferrin, cytokines such as tumor necrosis factor (TNF‐α), interleukin 8 (IL‐8) and nitric oxide (NO) were secreted. Secretion of TNF‐α peaked at 6 h of incubation in the presence of lactoferrin and then declined. About 80% of the maximum secretion of IL‐8 was observed at 6 h of incubation. The concentration of IL‐8 in the culture medium remained almost constant between 24‐72 h. In contrast, no siginificant effect on NO secretion was observed at 6 h, but a significant eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
1
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 13 publications
3
77
1
1
Order By: Relevance
“…One main mechanism for macrophage control of intracellular BCG involves production of NO [74,75], which can be stimulated by activation with IFN-γ [76]. Also, lactoferrin alone has been shown to increase macrophage NO production [77]. However, we observed no effect of lactoferrin on intracellular proliferation of BCG.…”
Section: Discussioncontrasting
confidence: 63%
“…One main mechanism for macrophage control of intracellular BCG involves production of NO [74,75], which can be stimulated by activation with IFN-γ [76]. Also, lactoferrin alone has been shown to increase macrophage NO production [77]. However, we observed no effect of lactoferrin on intracellular proliferation of BCG.…”
Section: Discussioncontrasting
confidence: 63%
“…Indeed, direct stimulation of CD3+ lymphocytes by Lactoferrin does not occur (unpublished observations). Addition of Lactoferrin to naïve macrophages increased TNF-α production, a stimulatory effect that has also been reported elsewhere [42]. The effect of Lactoferrin on activated macrophages is a more complex phenomenon.…”
Section: Discussionmentioning
confidence: 61%
“…More importantly, Lactoferrin as an adjuvant is capable of enhancing the T cell mediated DTH response to a variety of antigens including Mycobacterium bovis Calmette Guerin (BCG) [27,49,50]. The primary goal of these studies was to examine, in vitro, the effect of bovine Lactoferrin on cytokine production from activated and non-activated leukocyte populations [42], with focus on defining responsive phenotypes and identifying cytokines that can drive T cell differentiation, in particular IL-12 and IL-10. The secondary goal was to establish that Lactoferrin administered with a complex vaccine antigen would result in increased production of CD4+ T helper antigen-specific responses, a subject under active investigation [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactoferrin possesses a wide range of immunomodulatory activities [17][18][19] [20] [21] including promotion of the T-cell dominated DTH response towards BCG antigens [22,23], The ability of lactoferrin to enhance the generation of antigen specific DTH responses suggests that lactoferrin could promote development of specific T-cell responses against a complex antigen, such as BCG [24,25] The development of T-cell helper type 1 (T H 1) immunity is, in part, regulated by production of IL-12 [26,27]. A variety of in vivo studies have shown lactoferrin capable of increasing production of IL-12 [28][29][30].…”
Section: Introductionmentioning
confidence: 99%